PEMODELAN PENGARUH PEMOMPAAN SUMUR PRODUKSI PADA AKIFER DENGAN MUKA AIR TANAH MIRING - Ramli, Muhammad; Idris, Muhram Sula; Wihdah, Wihdah; Almuqarram, Aswad; Khaerunnisa, Hamdana (Politeknik Negeri Semarang, 2020)
The main issue in the utilization of ground water is always related to the decrease in water table or piezometric level. The decreasing of groundwater level is often accompanied by number of environmental impacts such as; subsidence, sea water intrusion, or reduced water from residents' wells and surface water bodies. Therefore, an experimental and numerical study was carried out to learn phenomena of cone depression resulted by groundwater production well. The experimental study of physical modeling used the S12-MKII Hydrology Study System equipment, and numerical modeling used Groundwater Modeling Software - Modflow. The modeling results were verified by analytical estimation. The results indicated that the groundwater withdrawn obtained with physical model and numerical simulation is bigger than estimated by analytical equation, particularly in estimating groundwater divide to a well.